A randomised trial of the effect of the glycine reuptake inhibitor Org 25935 on cognitive performance in healthy male volunteers. (14th January 2014) - Christmas, David; Diaper, Alison; Wilson, Sue; Rich, Ann; Phillips, Suzanne; Udo de Haes, Joanna; Sjogren, Magnus; Nutt, David
<x xml:space="preserve">Abstract</x> Objective Cognitive impairment is integral to many neurological illnesses. Specific enhancement of glutamatergic transmission may improve memory and learning. Org 25935 increases the synaptic availability of glycine, an obligate co‐agonist with glutamate at N‐methyl‐d‐aspartate receptors. We hypothesised that Org 25935 would acutely improve the learning and memory of healthy volunteers. Methods A randomised, double‐blind, parallel‐group, single‐dose study of Org 25935 and placebo was carried out. Thirty‐two healthy male volunteers took either 12‐mg Org 25935 or matching placebo and were later assessed with the manikin task, digit span and verbal memory tests. Systematic assessments of cardiovascular and adverse events were also taken. Results There was no effect of Org 25935 on reaction time, number of correct responses or learning (greater or slower improvement over successive tasks) compared with placebo. Org 25935 caused significantly more dizziness and drowsiness compared with placebo; these side effects were mainly mild. Conclusions A single dose of Org 25935 does not improve learning or memory in healthy male individuals. However, the drug was well tolerated, and it remains to be seen whether it would have a positive effect on cognition in patient groups with pre‐existing cognitive deficits. Copyright © 2014 John Wiley & Sons, Ltd.